THE INFLUENCE OF MOTIVATION, ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION WITH COMMITMENT AS AN INTERVENING VARIABEL IN GOVERNMENT AGENCY EMPLOYEES : LITERATUR REVIEW - Putri, Dika Hardiyani; Hadi, Syamsul; Septyarini, Epsilandri (International Conference on Humanity Education and Society (ICHES), 2024)
This article aims to understand in depth through literature review the relationshipbetween motivation, organizational support, and organizational culture on jobsatisfaction with commitment as an intervening variable. The research method usedis a systematic literature review (SLR) using 37 articles obtained from the GoogleScholar database using the keywords "motivation, organizational support,organizational culture, job satisfaction and commitment", then reviewed one by oneeach article obtained focusing on the effect of motivation, organizational supportand organizational culture on job satisfaction with commitment as an interveningvariable. The results of research from several literature reviews provide anunderstanding that motivation, organizational support and organizational culturehave a positive effect on job satisfaction and also have a positive effect on commitment. This literature also shows that commitment is expected to mediate therelationship between motivation, organizational support and organizational cultureto job satisfaction. The results of this discovery can be used as a reference for futureempirical research